Positive Discipline as A New Paradigm Alternative in Classroom Management: An Epistemological Study - Hermawan, Syarif; Novikasari, Ifada (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
The success of learning is determined by safe and comfortable classroom conditions for students. This condition is created if the teacher can manage the class by creating a positive and mutually respectful relationship between students and teachers. Positive discipline is an approach that focuses on positive reinforcement and reflection rather than punishment to manage student behavior. The aim of this research is to explore how teachers manage the classroom optimally by using a positive discipline approach in the classroom. Using an epistemological framework, this article aims to understand how positive discipline contributes to learning and can be applied in the context of classroom management. This research is a type of qualitative research. Data was collected through classroom observations, in-depth interviews with teachers and students, and analysis of related documents. The research results show that the application of positive discipline can increase student involvement in the learning process, reduce conflict, and improve the quality of teacher-student interactions. In addition, this research found that changing the classroom management paradigm towards positive discipline requires systemic support and a deep understanding of its basic principles. This study contributes to the development of positive discipline theory as well as offers practical recommendations for educators.